THE CULTURAL DIVERSITY OF PAKISTAN: HERITAGE, TRADITIONS, AND MODERN INFLUENCES - Sajid Aziz, Muhammad (Penerbit Lafadz Jaya, 2024)
Pakistan, a nation located at the crossroads of South Asia and Central Asia, boasts a rich tapestry of cultural traditions influenced by various historical events and ethnic groups. This paper explores the multifaceted nature of Pakistani culture, including its language, cuisine, music, and art forms. The paper delves into the historical roots of these cultural elements, examining how the interplay of indigenous practices, colonial history, and globalization has shaped contemporary cultural expressions in Pakistan. Furthermore, special attention is given to the regional diversity evident across the provinces, encompassing distinct customs and lifestyles. The findings highlight the resilience of traditional practices amidst modernity, showcasing how Pakistani culture remains vibrant and adaptive. This research contributes to the understanding of cultural dynamics in Pakistan and emphasizes the significance of cultural preservation in an era of rapid change.